Implementation Of the Notary's Duties and Positions Regarding the Presence of the Appeaser Refers to Decree Number 65/33-III/ PP-INI/2020 Dated March 17, 2020 - Witapratama, Muhammad Firdausy Maulana (Universitas Wijaya Kusuma Surabaya, 2021)
Concerns about Covid 19 by notaries in doing the Deed. This study aims to examine the Implementation of the Notary Position in Doing Deeds Before and during the Covid-19 Pandemic Period, and to Assess Obstacles in the Duties of Notary Positions in Doing Deeds during the Covid-19 Pandemic Period). The type of research used by the author is descriptive type research. Descriptive research is a problem-solving procedure investigated by describing or describing the current state of the subject and object of research based on existing facts. The results of the research in the Assignment of Notary Positions in Doing Deeds Before and during the Covid 19 Pandemic Period differed from the difference in the health protocol and the presence of the appeasers based on SK Number 65/33-III/ PP-INI/2020 dated March 17, 2020, regarding the matter referred to In the main point of the letter, the Central Management of the Indonesian Notary Association (PP-INI) and all of its staff expressed concern over the massive development of the spread of Covid-19 which directly affected the implementation of the duties of a Notary public in providing services to the public and in this regard, this PP urges all members to follow the health protocols set by the government to overcome the spread of Covid-19.Keywords: CoronaViruses, Notary, Decree.